2013
DOI: 10.1111/wre.12025
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of molecules between parasitic plants and their hosts

Abstract: Parasitic plants have evolved various methods of invading host plants. Some invade aerial parts, whereas others invade the roots to obtain necessary nutrients for their development. Phelipanche and Orobanche spp. (broomrapes) and Cuscuta spp. (dodders) are holoparasitic plants that subsist on roots and shoots, respectively, of a variety of agricultural crops. These weeds are able to connect directly with the vascular system of the host, thereby acquiring the water, minerals and carbohydrates necessary for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…Upon establishment of a xylem‐to‐xylem connection, the parasite can extract host metabolites, nutrients and water from its host (e.g. Aly, ). In some cases, phenolic substances or lignins can be observed on the host roots where the parasite attempts to penetrate, indicating the existence of a host plant defence reaction (Neumann et al ., ).…”
Section: What Do We Know About the Plant Species R Fistulosa?mentioning
confidence: 99%
“…Upon establishment of a xylem‐to‐xylem connection, the parasite can extract host metabolites, nutrients and water from its host (e.g. Aly, ). In some cases, phenolic substances or lignins can be observed on the host roots where the parasite attempts to penetrate, indicating the existence of a host plant defence reaction (Neumann et al ., ).…”
Section: What Do We Know About the Plant Species R Fistulosa?mentioning
confidence: 99%
“…It obtains its resources entirely from its host plants (Dawson et al 1994). Cuscuta-infested plants gradually become weak, resulting in decline in growth and yield (Aly 2013). In addition to its impact on ornamentals, native plants and forage crops, it has been reported that Cuscuta can suppress or kill vegetables and weeds (Fathoulla and Duhoky 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Natural extracts from plants and other organism for protecting crops from pathogens and pests have recently been reported. They protect plants without negatively affecting the growth and yield (Kapooria et al 2007, Aly 2013). An effective method of achieving crop protection is inducing resistance by activating natural protection system with elicitors that are environmentally safe.…”
Section: Introductionmentioning
confidence: 99%
“…Host exhaustion caused by weedy Phelipanche spp. results in huge losses of crop yield and influences final fruit quality (Aly, 2013). Many different strategies have been tested to eliminate parasite from the environment, such as manual weeding, using herbicides or host plant breeding programs for parasite resistance, but they do not provide sufficient crop protection.…”
Section: Introductionmentioning
confidence: 99%